2002
DOI: 10.1161/01.res.0000018625.25212.1e
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Radical-Induced Acute Diastolic Dysfunction Is Due to Calcium Overload via Reverse-Mode Na + -Ca 2+ Exchange

Abstract: Abstract-Hydroxyl radicals (OH) are involved in the development of reperfusion injury and myocardial failure. In the acute phase of the OH-mediated diastolic dysfunction, increased intracellular Ca 2ϩ levels and alterations of myofilaments may play a role, but the relative contribution of these systems to myocardial dysfunction is unknown. Intact contracting cardiac trabeculae from rabbits were exposed to OH, resulting in an increase in diastolic force (F dia ) by 540%. Skinned fiber experiments revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 55 publications
(66 reference statements)
8
60
0
4
Order By: Relevance
“…Other than the effects of membrane lipid peroxidation causing cellular environmental changes, the membrane-embedding enzymes, such as Na + -K + ATPase, Ca 2+ ATPase and 5′-nucleotidase, may be attacked directly by oxygen radicals (59,69,70). It has been shown that modification of the sulfhydryl groups of these enzymes by an oxygen radical reduces their activity (70).…”
Section: Mechanisms Of Mechanical Disturbance In Iron Overload Cardiomentioning
confidence: 99%
See 1 more Smart Citation
“…Other than the effects of membrane lipid peroxidation causing cellular environmental changes, the membrane-embedding enzymes, such as Na + -K + ATPase, Ca 2+ ATPase and 5′-nucleotidase, may be attacked directly by oxygen radicals (59,69,70). It has been shown that modification of the sulfhydryl groups of these enzymes by an oxygen radical reduces their activity (70).…”
Section: Mechanisms Of Mechanical Disturbance In Iron Overload Cardiomentioning
confidence: 99%
“…Oxygen free radicals also have a direct effect on decreased cardiac SR Ca 2+ ATPase activity (72), which may be responsible for diastolic failure. In the in vitro study by Zeitz et al (69), hydroxyl radical-exposed rabbit heart muscle was demonstrated to have calcium overload (via Na + -Ca 2+ exchange), with an acute diastolic dysfunction. These mechanisms may explain the pathophysiology of early cardiac dysfunction in iron overload cardiomyopathy.…”
Section: Mechanisms Of Mechanical Disturbance In Iron Overload Cardiomentioning
confidence: 99%
“…More interestingly, several groups have reported degradation products of TnI in serum of patients after acute myocardial infarction (AMI) [35][36][37]. Degradation products of TnT were also found both in animal models of ischemia/reperfusion injury [38,39] and in serum of patients with AMI [40,41]. In 2000, TnI and TnT have been approved as the biomarkers for AMI diagnosis [42], and several kits have been commercially developed and used in clinical studies [43][44][45].…”
Section: Degradationmentioning
confidence: 99%
“…Protein degradation often involves significant molecular weight (MW) reduction, which can be readily detected by 1-D-gel separation followed by Western blot analysis [31,32,[34][35][36][37][38][39][40][41]. Comparative 2-DE was also used to study proteomic changes on a broader scale, and PMF can be employed to identify changed proteins [46].…”
Section: Degradationmentioning
confidence: 99%
“…O aumento do estresse oxidativo, presente na insuficiência cardíaca, pode proporcionar um aumento da tensão diastólica, proteólise de miofilamentos e diminuição da contratilidade (78). Estes efeitos estão associados à sobrecarga de cálcio que é resultado, dentre outros fatores, de danos ao retículo sarcoplasmático.…”
Section: Efeitos Isolados Do Treinamento Físico E Do Tratamento Com unclassified